Palæstina tur/retur - dansk zionismes Palæstina-rødder - Zuckerman, Maja Gildin (Rambam. Tidsskrift for jødisk kultur og forskning, 2017)
A Roundtrip to Palestine – the Roots of Danish Zionism in Palestine Louis Herman Frænkel (1868-1935) founded the Danish Zionist Association (Dansk Zionistforening) and chaired the association until the First World War. Through his Zionist leadership, his role as a community activist as well as a public commentator, Frænkel became known in both Denmark and abroad as the personification of (early) Danish Zionism. The article presents new research on the emergence of Danish Zionism, especially the relationship between what was considered “Jewish” and “Zionist” in this period. The focus here is on Frænkel’s journey to Palestine in the spring of 1897 and the implications the journey had on the dissemination of Zionism within the Danish-Jewish public sphere. The journey displays Zionist emergence as a process which was constantly expanding the existing and future opportunities for a Jewish home and community that extended far beyond the borders of the nation state.